BRANDING DAN PROMOSI WISATA ALAM SERTA BUDAYA DESA PRINGGASELA SELATAN BERBASIS MEDIA DIGITAL - Muliatul Qomari, Muna; Ikhsan Cahyadi, Ikhsan Cahyadi; Haq, M Iqbalul; Riza Afwa, Muhamad; Amida, Rani; Ramdani, Nadia; Sulinantangi, Delji; Rosalinda; Af’idah; Budi Rahmatullah, Tri; Nurmayanti, Siti; Ikhsan Cahyadi, Muhammad (Jurnal Wicara, 2025)
The current development of the digital era is marked by the increasingly massive useof social media. Social media has become a very effective tool for promoting variousproducts and services, including tourist destinations. Appropriate image management andmarketing strategies through digital platforms can have a significant impact on increasingthe popularity of a tourist or cultural destination. Branding is done to convey the uniquenessof products, services or tourism to the target market. In carrying out branding, it mustinclude brand, identity and values. Meanwhile, when carrying out promotions, you must payattention to relevant social media trends and targets. This digital media-based branding andpromotion activity uses direct socialization and training methods which aim to provideeducation as well as skills for South Pringgasela youth as future tourism managers throughsocial media such as Facebook, Instagram, WhatsApp and TikTok.